Thermochromic aggregation-induced dual phosphorescence via temperature-dependent sp 3-linked donor-acceptor electronic coupling - Tao Wang (Nature Portfolio, 2021)
Aggregation-induced emission (AIE) has proven to be a viable strategy to achieve highly efficient room temperature phosphorescence (RTP) in bulk by restricting molecular motions. Here, the authors present an RTP design strategy by combining the concept of AIE and donor-acceptor motif and demonstrate unusual thermochromic dual phosphorescence.